Uncovering the Holocaust the international reception of night and fog - Knaap, Ewout van der 1965- (Wallflower Press, 2006)
The articles in this book provide details and insightful observations on the political and social reception of 'Night and Fog'. They offer a new dimension to scholarship on the film and its place in the debate on memory and the Holocaust.
Keywords: Resnais, Alain <1922->; Nuit et brouillard (Motion picture); Nuit et brouillard; Weltkrieg (1939-1945); Holocaust, Jewish (1939-1945), in motion pictures; World War, 1939-1945 -- Motion pictures and the war; Rezeption; Aufsatzsammlung